Establishing criteria for higher‐level classification using molecular data: the systematics of Polyommatus blue butterflies (Lepidoptera, Lycaenidae). (10th September 2012) - Talavera, Gerard; Lukhtanov, Vladimir A.; Pierce, Naomi E.; Vila, Roger
Abstract Most taxonomists agree on the need to adapt current classifications to recognize monophyletic units. However, delineations between higher taxonomic units can be based on the relative ages of different lineages and/or the level of morphological differentiation. In this paper, we address these issues in considering the species‐rich Polyommatus section, a group of butterflies whose taxonomy has been highly controversial. We propose a taxonomy‐friendly, flexible temporal scheme for higher‐level classification. Using molecular data from nine markers (6666 bp) for 104 representatives of the Polyommatus section, representing all but two of the 81 described genera/subgenera and five outgroups, we obtained a complete and well resolved phylogeny for this clade. We use this to revise the systematics of the Polyommatus blues, and to define criteria that best accommodate the described genera within a phylogenetic framework. First, we normalize the concept of section (Polyommatus) and propose the use of subtribe (Polyommatina) instead. To preserve taxonomic stability and traditionally recognized taxa, we designate an age interval (4–5 Myr) instead of a fixed minimum age to define genera. The application of these criteria results in the retention of 31 genera of the 81 formally described generic names, and necessitates the description of one new genus (Rueckbeilia gen. nov.). We note that while classifications should be based on phylogenetic data, applying a rigid universal scheme is rarely feasible. Ideally, taxon age limits should be applied according to the particularities and pre‐existing taxonomy of each group. We demonstrate that the concept of a morphological gap may be misleading at the genus level and can produce polyphyletic genera, and we propose that recognition of the existence of cryptic genera may be useful in taxonomy.